Legislación e higiene veterinaria : Medellín, 1913-1926 (2010)
ABSTRACT: This article contributes to the history of veterinary hygiene and the salubrity of animal-based foods in Medellin between 1913 and 1926. During this period, the agricultural and ranching frontier in Antioquia expanded and Medellin, with a growing population, started to become a pole of economic development and the principal livestock market in Colombia. To assist this process, national, departmental, and municipal authorities regulated animal health, veterinary instruction, and encouraged the growth of the livestock industry. Primary sources, such as correspondence and official newspapers, show that the hygienist discourse was initiated by economic and political elites from Antioquia and that the sanitary problems regarding meat and milk were resolved in Medellin by having the city take over the companies charged with providing these foodstuffs.